Measuring the potential of augmented reality in civil engineering. (December 2015) - Meža, Sebastjan; Turk, Žiga; Dolenc, Matevž
Abstract: Recently building information models have substantially improved the explicit semantic content of design information. Information models are used to integrate the initial phases of project development. On the construction site, however, the designs are still mostly represented as line-based paper drawings or projections on portable displays. A generic technology that can integrate information and situate it in time, place and context is augmented reality. The specific research issues addressed are (1) does augmented reality have a potential use in civil engineering, (2) how big – in comparison to other technologies - is this potential and (3) what are the main barriers to its adoption. The generic research issue was to develop a methodology for evaluation of potentials of technology. A prototype was built. It was tested on a real construction site to evaluate the potential of its use using the action-research method. A set of structured interviews with potential users was then conducted to compare the prototype to conventional presentation methods. Using this methodology it has been found out that augmented reality is expected to be as big a step as the transition from 2D line drawings to photorealistic 3D projections. The main barrier to the adoption is immature core virtual reality technology, conservative nature of construction businesses and size of building information models. Highlights: Well-formed digital models, such as BIM, are a prerequisite for construction AR. Augmented reality can contribute to the understanding of project documentation. Construction AR needs to be developed in parallel with conventional methods. Construction AR can help better understand construction 3D models.